Anticancer Mechanisms of Zoledronic Acid-Based Graphene Oxide Nanoparticles for Prostate Cancer Bone Metastases Treatment - Rasheed, Hala Abdulkareem; Alsahlanee, Rasha; Khalfa, Hydar Muhsin (Iraqi Journal of Science, 2022)
Bone metastases are the main reason for death in males suffering from advanced prostate cancer. This study aimed to create zoledronic acid and graphene oxide conjugation for anticancer therapy. The process of conjugation was confirmed by several characterization methods including UV-VIS spectrophotometry, Fourier Transform Infrared Spectroscopy (FTIR), and atomic force microscope (AFM). the cytotoxicity of 400, 600, and 800 μg/ml to each GO, ZOL, and ZOL-GO was evaluated on a human hepatic cell line (WRL 68) and human prostate cancer cell line (PC3) using an MTT assay. The antitumor mechanisms of ZOL-GO were examined by cell cycle analysis. The results demonstrated That ZOL-GO caused a reduction in the cell viability of WRL 68 and PC3, with IC50 values of about 932.9 and 787.9 µg/ml respectively. The cell cycle distribution was evaluated after treating the prostate cancer cells (PC3) with 800µg/mL of ZOL-GO, the results showed the presence of a highly significant arresting effect in the G1 phase (P≤ 0.002) than the untreated cells (control). Our findings demonstrate the potential antitumor activity of using GO as a nanocarrier to improve the therapeutic efficacy of prostate cancer.